The effect of stress inoculation on decrease of PTSD symptoms in veterans - E. Ahmadzadeh Aghdam (طب جانباز, 2013)
Purpose: The aim of this study was to know the effectiveness of stress inoculation on decrease of post traumatic stress disorder in Iran- Iraq (Persian Gulf) war.